Mot1 Redistributes TBP from TATA-Containing to TATA-Less Promoters - Zentner, Gabriel E. (American Society for Microbiology, 2013)
The Swi2/Snf2 family ATPase Mot1 displaces TATA-binding protein (TBP) from DNA in vitro, but the global relationship between Mot1 and TBP in vivo is unclear. In particular, how Mot1 activates transcription is poorly understood. To address these issues, we mapped the distribution of Mot1 and TBP on native chromatin at base pair resolution. Mot1 and TBP binding sites coincide throughout the genome, and depletion of TBP results in a global decrease in Mot1 binding. We find evidence that Mot1 approaches TBP from the upstream direction, consistent with its in vitro mode of action. Strikingly, inactivation of Mot1 leads to both increases and decreases in TBP-genome association. Sites of TBP gain tend to contain robust TATA boxes, while sites of TBP loss contain poly(dA-dT) tracts that may contribute to nucleosome exclusion. Sites of TBP gain are associated with increased gene expression, while decreased TBP binding is associated with reduced gene expression. We propose that the action of Mot1 is required to clear TBP from intrinsically preferred (TATA-containing) binding sites, ensuring sufficient soluble TBP to bind intrinsically disfavored (TATA-less) sites.